The conceptual review of the Influencing factors on student loan initiation in the Higher Education Institutions (HEIS) / Nor Effuandy Pfordten … [et al.] - Pfordten, Nor Effuandy; Ali, Md. Jafor; Sabli, Norhaila; Ab Rashid, Norasekin; Bhuiyan, Abul Bashar (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The higher education loan creates immense opportunities for students, especially those from low-income households, for acquiring better knowledge, skills, expertise, creative abilities, and intelligence that bring utmost qualitative changes in life. This comprehensive empirical review study attempts to understand and evaluate the foremost influences and impacts of student loans initiation in Higher Education Institutions (HEIs). The present study adopts re-examining the influences of student loan initiation in HEIs and its impacts from the course of existing and conspicuous research works and works of literature. The study observes impetuses behind student loans initiation in the HEIs are; costs-sharing among the governments, students, and households; enhancing accessibility on social equity consideration, developing human resources as per the demand of the labour market, and increasing financial viability of the HEIs. Following the above influences, the study further reveals that student loans' effective disbursement and management can avoid delinquency problems and bring equitable impacts in society. Implications for future extensive research related to influences and impacts of higher education loans are offered.